IMPLEMENTASI KEBIJAKAN BANK SAMPAH DI KECAMATAN RAPPOCINI KOTA MAKASSAR - Nurharsyah Khaer Hanafie; Muhammad Sudirman; Delliar Ramadan (Jurnal Tomalebbi, 2023)
This research was conducted with the aim of knowing and finding 1). Implementation of waste bank policies in Rappocini District, 2). Knowing and discovering the contribution of waste banks to the environment, social and economy of the community in Rappocini District. The type of research used is phenomenological research. The data collection techniques used are interviews, observation and documentation. The data collection process carried out by researchers included: data collection, data reduction, data presentation and drawing conclusions. The research results show 1). The implementation of a waste bank based on research in the Rappocini District has been running well, this can be seen from the existence of a waste bank in the Rappocini District. However, in terms of resources, they are still considered inadequate due to the existence of waste disposal banks which have stopped operating because there has been no reorganization and the management has left. This is due to a lack of public awareness and interest in participating in waste collection. 2). The waste bank has contributed a lot to the environment, social and economy of the people in Rappocini District. In terms of the environment, for example, there has been a decrease in the transportation of waste that will be disposed of at the Final Disposal Site (TPA) because people whose social activities are starting to change are the ones who initially throw it away, since the existence of a waste bank, people prefer to store it and then exchange it for money in the form of savings or recycling. The waste becomes goods with sale or economic value so that it has an impact on the community's economy in meeting their daily needs.